Analisis Pemeriksaan dalam Meningkatkan Kepatuhan Wajib Pajak Badan di Kantor Pelayanan Pajak Pratama Jakarta Tanah Abang Satu Tahun 2016-2018 - Adriani Adriani; Alief Ramdan (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The particular phenomenon faced is the implementation of the self-assessment system in Indonesia which is expected to increase public awareness and honesty as taxpayers to self-calculate the amount of tax payable and not payable. But it turns out that there are still many taxpayers who are not compliant in paying their taxes. The purpose of this study was to analyze tax audit in increasing corporate taxpayer compliance, and to analyze the driving and inhibiting entities of tax audit in increasing corporate taxpayer compliance. This study used the theory from Prof. Dr. Safri Nurmantu, M.Sc. The research approach used in this study was descriptive qualitative by conducting observations, interviews, and documentation since this study generated the conclusion in the form of describing the data in detail and the data were not in the form of numbers.The results of the study showed that the tax audit in increasing corporate taxpayer compliance at Pratama Tax Office Tanah Abang I Jakarta hadgone well, it can be seen that in the audit conducted by the Tax Office the level of taxpayer compliance had increased.The obstacles of the tax audit at Pratama Tax office Tanah Abang I Jakarta were in the form of the indications or triggers for taxation non-compliance such as invoices, financial reports or data from the regional office and the taxpayers themselves who were less cooperative.For these reasons, the researcher hopes that taxpayers can be more cooperative by participating in the audit process.The particular phenomenon faced is the implementation of the self-assessment system in Indonesia which is expected to increase public awareness and honesty as taxpayers to self-calculate the amount of tax payable and not payable. But it turns out that there are still many taxpayers who are not compliant in paying their taxes. The purpose of this study was to analyze tax audit in increasing corporate taxpayer compliance, and to analyze the driving and inhibiting entities of tax audit in increasing corporate taxpayer compliance. This study used the theory from Prof. Dr. Safri Nurmantu, M.Sc. The research approach used in this study was descriptive qualitative by conducting observations, interviews, and documentation since this study generated the conclusion in the form of describing the data in detail and the data were not in the form of numbers.The results of the study showed that the tax audit in increasing corporate taxpayer compliance at Pratama Tax Office Tanah Abang I Jakarta hadgone well, it can be seen that in the audit conducted by the Tax Office the level of taxpayer compliance had increased.The obstacles of the tax audit at Pratama Tax office Tanah Abang I Jakarta were in the form of the indications or triggers for taxation non-compliance such as invoices, financial reports or data from the regional office and the taxpayers themselves who were less cooperative.For these reasons, the researcher hopes that taxpayers can be more cooperative by participating in the audit process.